Pemikiran Muhammad Asad tentang Negara Islam - Rahman, Muhammad (Syams, 2023)
This research was conducted to find out how Muhammad Asad'sperspective on the concept of Islamic government as a reflection of the formation of theIslamic State of Pakistan. The form of government system in Islam as an idealsystem among the Ummah, of course, has different views. As was the case whenPakistan officially broke away from India and became independent in 1947. At thebeginning of the journey as a new country, many debates took place betweenintellectuals or nationalists and religious people or ulama. Each group agreed tomake Islam the hallmark of the State of Pakistan, but the difference in views thatoccurred was when the Nationalists proposed Islam as the hallmark of the state butthe laws and style of government followed the West. Of course, this was opposed bythe ulama who wanted Islam to be the whole foundation of the state as the purpose ofthe establishment of Pakistan from the beginning. The problem occurred partlybecause an influential figure in the formation of Pakistan died one year afterindependence. So this made Pakistan's immature state as a new country, ambiguous.On the other hand, several Muslim intellectuals were present to help the developmentof the Islamic State of Pakistan, such as Leopold Weiss or Muhammad Asad. Thisresearch is a library research that uses the historical method, with four stages, namelyfirst, heuristics by collecting several sources, both primary sources and secondarysources. Then second, source verification by conducting external criticism and internalcriticism. Third, interpretation by interpreting or by analyzing some of the sourcesobtained. And finally, historiography, namely d by writing down the results of theresearch that has been obtained. The results showed that Muhammad Asad in someof his works showed the concept he gave about the Islamic government system. Thenthrough the concept he put forward also influenced the formation of the Islamic Stateof Pakistan. Despite being a Mualaf, Asad was able to explore Islam and love allthings related to Islam. In addition to contributing to the concept of Islamicgovernment used in Pakistan, Asad also did a lot of Hadith interpretation to provideconcepts of thought on education and gender. So that Muhammad Asad has animportant role in Pakistan, especially during the formation of the State.